Studi Kecermatan Alat Ukur Kebulatan (Roundness Tester Mechine) Produksi Laboratorium Pengukuran Universitas Riau - Indro Parma; Adhy Prayitno; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Accuracy is the closeness or the accuracy of the measurement results with the actual value. Accuracy can also mean a measure of the closeness results of the analysis of the actual invitation analyte levels. Accuracy is vital that must be fulfilled and owned by any measurement tool, use the measuring instrument that has high accuracy and good will produce accurate measurement data and other wise use measuring devices are not accurate, do not meet the standards of the results obtained will not be accurate. This study aims to determine the value of the mandrel roundness deviation, roundness accuracy Measuring Equipment (Roundness Tester Machine) and large deviations in the roundness measuring instrument (Roundness TesterMachine) (instrument error) and the operator or gauges (human error). From the results, the large stroundness deviation value for minimum circumscribed circle is 0,474 mm, maximum inscribed circle 0,417 mm, minimum zone circle 0,495 mm, least squares circle 0,207 mm, for the value of sphericity (roundness) for the smallest outer for minimum circumscribed circleis 0,003 mm, maximum inscribed circle 0,003 mm, minimum zone circle is 0,003 mm, least squares is 0,001 mm. Value accuracy roundness measuring instrument (Roundness TesterMachine) in position 1 = 0,006 mm, position 2 = 0,006 mm, position 3 = 0,011 mm, position 4 = 0,018 mm, position 5 = 0,003 mm, position 6 = 0,018 mm, position 7 = 0,021 mm, position 8 = 0,031 mm, position 9 = 0,002 mm, position 10 = 0,001 mm and error measuring instrument (instrument error) is the largest 0,02944 mm or 18,871% and the smallest deviation is 0,00029 mm or 0,225%. Operator error or measuring (Human Error) for first test (human) 22%, second test 5,33%, third test 182%, fourth test 187%, fifth test 58%.Keywords: Accuracy, Deviation, Human error, Roundness Tester Machine.